Rekontruksi Penegakan Hukum Tindak Pidana Penipuan Di Kabupaten Gorontalo - Ilham, Ilham (Institut Agama Islam Negeri Bone, 2023)
ABSTRACT The results of this study indicate that, (1) The factors for the occurrence of criminal acts of fraud in the Legal Area of the North Gorontalo Police are due to factors within the perpetrators and factors outside the perpetrators, (2) The efforts of the North Gorontalo Police in enforcing the law on fraud crimes are with preventive/pre-active efforts and repressive efforts. Preventive/pre-ensive efforts are carried out by way of legal counseling or outreach at both the community level and in government agencies. Meanwhile, the repressive efforts of the North Gorontalo Police in the form of the application of criminal law. In this writing, the efforts made by the North Gorontalo Police began with investigations and collaboration with relevant agencies and ultimately the implementation or enforcement of criminal law, namely article 378 of the Criminal Code.